Repeat hepatectomy versus thermal ablation therapy for recurrent hepatocellular carcinoma: a systematic review and meta-analysis - Dong, Renhua; Zhang, Ting; Wan, Wenwu; Zhang, Hao (Frontiers in Oncology, 2024)
Background: This meta-analysis was conducted to assess the survival benefits of repeat hepatectomy (RH) and thermal ablation therapy (TAT) in managing recurrent hepatocellular carcinoma (HCC).A comprehensive search was conducted in the PubMed, SinoMed, Embase, Cochrane Library, Medline, and Web of Science databases using relevant keywords to identify all studies published on this specific topic. Pooled odds ratios (ORs) with corresponding 95% confidence intervals (CIs) were estimated using a fixed-effects model.This meta-analysis included a total of 21 studies, comprising 2580 patients with recurrent HCC, among whom 1189 underwent RH and 1394 underwent TAT.Meta-analysis results demonstrated that the RH group exhibited superior overall survival (OS) (HR=0.85, 95%CI 0.76∼0.95, P=0.004) and recurrence-free survival (RFS) (HR=0.79, 95%CI 0.7 ∼ 0.9, P ＜ 0.01) compared to the TAT group. Regarding postoperative complications, the TAT group experienced fewer complications than the RH group (OR=3.23, 95%CI 1.48∼7.07, P=0.003), while no significant difference in perioperative mortality was observed between the two groups (OR=2.11, 95%CI 0.54 ∼8.19, P=0.28).The present study demonstrates that, in comparison to TAT, RH may confer superior survival benefits for patients with recurrent HCC.